Development of Interactive Learning Media Using Lectora Inspire on Motion and Force Materials in Junior High School - Fauziah Hafni; Azhar Azhar; Muhammad Nasir (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
This research aims to develop a valid interactive learning media using the Lectora Inspire application related to the concept of motion and force in learning in junior high school. The research applies the type of research and development (R&D), using the ADDIE model until the development phase. The research instrument used was a validation sheet for the development of interactive learning media. The use of the validation sheet instrument has been validated by 3 experts to determine the validity of the media as a research data collection technique. Data analysis was carried out by converting the media validation sheet using a Likert scale to obtain quantitative data. Descriptive analysis used descriptive statistics as a data analysis technique. The results obtained in every aspect of design, pedagogy, content, and ease of use are at a high level and very high with a valid category. So that the interactive media for learning physics using the Lectora inspire application for motion and force material in junior high school has been valid and worthy to be used as a learning resource that can help students understand motion and force material.